Fe/TiO2-GO nanosheets as two-dimensional photocatalyst in the application of rhodamine B photodegradation - Yunarti, Rika Tri; Emanuel, Efan; Buhori, Achmad; Apriandanu, Dewangga Oky Bagus; Dahnum, Deliana; Ha, Jeong-Myeong (Elsevier BV, 2025)
The environmental problems resulting from the wastewater produced by textile industries are getting more concerning over time as the organic pollutant molecules in this wastewater are persistent, demanding to be naturally degraded, and highly toxic. One feasible and preferred solution to this problem is achieved through catalyzed photodegradation. Hence, this study attempted to synthesize a photocatalyst material based on Fe/ TiO2-GO nanosheets and investigate its photocatalytic performance toward rhodamine B degradation. The introduction of GO to TiO2 nanosheets and the doping of Fe metal resulted in a lower optical band gap of Fe/ TiO2-GO, which allowed the material to require less minimum energy to undergo photocatalysis. Further structural characterization was also undertaken to assess the chemical and physical characteristics of the photocatalyst. From the photodegradation experimental results, the Fe/TiO2-GO nanosheets showed the highest degradation percentage and kinetic reaction rate compared with the other control materials, including TiO2-GO and bare TiO2, as well as graphene oxide. This indicates that Fe/TiO2-GO nanosheets as a photocatalyst indeed have improved activity over the constituent materials. Moreover, the photocatalyst in this study exhibited excellent reusability, where the degradation percentage decreased by 3.5 % after reusing the catalyst five times.